Pertanggungjawaban Pidana Terhadap Tindak Pidana Penganiayaan Yang Dilakukan Oleh Anggota Tentara Nasional Indonesia (Studi Putusan Nomor 91-K/PM.III-12/AD/VI/2022) - Devina Alyssa Anandyra; Rehnalemken Ginting; Riska Andi Fitriono (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2026)
This study examines and examines related issues, first, the considerations of judges in handling criminal acts of assault committed by members of the Indonesian National Armed Forces against their subordinates. Second, it examines criminal liability for criminal acts of assault committed by members of the Indonesian National Armed Forces against their subordinates. This study uses normative legal research methods that are both prescriptive and applied, with a statutory approach, a case approach, the criminal liability approach in the Criminal Code (KUHP), and a conceptual approach. The data collection technique used was a literature study, with research instruments consisting of court decisions, laws and regulations, and scientific literature. Furthermore, the analytical technique used was a deductive method. This study concludes that, first, judges should not only consider criminal liability for the direct perpetrator but also assess the possibility of criminal liability for the commander under Articles 129 and 132 of the Criminal Code. The existence of a command relationship between the perpetrator and the commander, the commander's knowledge of the violence that occurred, and indications of failure to carry out their supervisory, development, and prevention functions towards subordinates are relevant grounds for applying command liability. Second, criminal liability in the military environment still focuses on the direct perpetrator (direct perpetrator liability) as regulated in the Criminal Code, because the concept of command responsibility has not been explicitly regulated in the Indonesian military criminal law system.